InSAR Signal and Data Processing - Xing, Mengdao; Lu, Zhong; Yu, Hanwen (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Synthetic aperture radar (SAR) interferometry (InSAR) is an important remote sensing technology used for topographic mapping and deformation monitoring, and has created a new type of radar datum that has significantly evolved during the last couple of decades. This book includes the latest InSAR studies published in the Special Issue "InSAR Signal and Data Processing" of Sensors. We hope that readers of all levels will be able to gain a better understanding of InSAR as well as the when, how, and why of applying this technology.